Gambaran Histopatologi Pankreas Tikus Hiperglikemia setelah Mengkonsumsi K-Karagenan dan í-Karagenan - Lestahari Rahayu; Rahma Damayanti; Thamrin Wikanta (Fakultas Farmasi Universitas Pancasila, 2006)
Research on the effect of K-carrageen and i-carrageen feeding on the representation of pancreatic B-cell histopathology of hyperglycemic rat has been carried out. Rats were previously damaged by aloxan monohydrat induction. There were 6 groups of rats, each group containing 5 animals. Group I normal control, group II negative control, group III 1st positive control, group IV 2nd positive control, group V K-carrageen treatment, group VI i-carrageen treatment. Group I, II, IV, V, and VI, were given orally, while group III was given subcutaneously. All the treatments were given during 15 days. All the rats were then killed and pancreatic hystopathology were carried out. The results revealed that aloxan monohydrat induction resulting the rat pancreatic weight reduction in all treatment groups. The ratio of rat body weight to the pancreatic weight was not significant difference in all treatment groups. Insulin injection was unable to increase the size of Langerhans islet and unable to support the recovery process of pancreatic damaged due to aloxan induction. On the other hand, chlorpropamide, K-carrageenan, and i-carrageenan were able to increase the size of Langerhans islet because they can support the recovery process of pancreatic organ damaged due to aloxsan induction. Insulin injection was unable to increase the ratio of Langerhans islet diameter to the amount of B-cells. While, chlorpropamide, K-carrageenan, and i-carrageenan were able to increase the ratio of Langerhans islet diameter to the amount of ß-cells. The macroscopic observation revealed that there was a black spot on the rat intestine receiving carrageen.